Optimal Control of Time-Periodic Navier-Stokes-Voigt Equations. (2nd October 2020) - Anh, Cung The; Nguyet, Tran Minh
Abstract: We consider a quadratic optimal control problem for the 3D Navier-Stokes-Voigt equations with periodic inputs. We prove the existence of optimal solutions, then establish necessary and sufficient optimality conditions. We also define semidiscrete-in-time approximations for the optimal control problem and then prove the existence of a subsequence that converges to an optimal solution.